EVALUATION OF TECHNICAL STATE OF GAS TURBINE PLANT ACCORDING TO THE RESULTS OF THE CONSTRUCTION OF THE PIVOT THROTTLE CHARACTERISTICS - A. R. Zagretdinov; R. I. Kamaev; V. I. Kruglov; V. N. Loginov (Известия высших учебных заведений: Проблемы энергетики)
The use of energy of gas turbine units recognized promising and is becoming more common. The need to improve the efficiency of their operation has led to the urgency of the problem assessment of the current technical condition. One approach to solving this problem is the method of construction of the pivot throttle characteristics (SDH), which found successful application in many power devices and has been improved within modern aviation technologies. The approach to determining the health of gas turbine engine based on the construction of SDH proposed method of increasing the reliability of calculation results. The methodology of trust-building corridors based on the universal modeling algorithm to determine the form and parameters of the distribution law of the experimental data depending on the specific test conditions.